Differences in sustained alterations in protein expression between livers of mice exposed to high-dose-rate and low-dose-rate radiation. (15th February 2017) - Nakajima, Tetsuo; Wang, Bing; Ono, Tetsuya; Uehara, Yoshihiko; Nakamura, Shingo; Ichinohe, Kazuaki; Braga-Tanaka, Ignacia; Tanaka, Satoshi; Tanaka, Kimio; Nenoi, Mitsuru
Abstract: Molecular mechanisms of radiation dose-rate effects are not well understood. Among many possibilities, long-lasting sustained alterations in protein levels would provide critical information. To evaluate sustained effects after acute and chronic radiation exposure, we analyzed alterations in protein expression in the livers of mice. Acute exposure consisted of a lethal dose of 8 Gy and a sublethal dose of 4 Gy, with analysis conducted 6 days and 3 months after irradiation, respectively. Chronic irradiation consisted of a total dose of 8 Gy delivered over 400 days (20 mGy/day). Analyses following chronic irradiation were done immediately and at 3 months after the end of the exposure. Based on antibody arrays of protein expression following both acute lethal and sublethal dose exposures, common alterations in the expression of two proteins were detected. In the sublethal dose exposure, the expression of additional proteins was altered 3 months after irradiation. Immunohistochemical analysis showed that the increase in one of the two commonly altered proteins, MyD88, was observed around blood vessels in the liver. The alterations in protein expression after chronic radiation exposure were different from those caused by acute radiation exposures. Alterations in the expression of proteins related to inflammation and apoptosis, such as caspase 12, were observed even at 3 months after the end of the chronic radiation exposure. The alterations in protein expression depended on the dose, the dose rate, and the passage of time after irradiation. These changes could be involved in long-term effects of radiation in the liver.